22=u-53

Simple and best practice solution for 22=u-53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22=u-53 equation:



22=u-53
We move all terms to the left:
22-(u-53)=0
We get rid of parentheses
-u+53+22=0
We add all the numbers together, and all the variables
-1u+75=0
We move all terms containing u to the left, all other terms to the right
-u=-75
u=-75/-1
u=+75

See similar equations:

| 4y2-13=y2+14 | | X(b)=30 | | 5/2x+18=8x | | 5(x-3)=3(x-1)+2x | | 14-4x=17.8 | | 3(4x-9)+4=2(5x-7)+2x | | 6(x+9)=116 | | 1/6(a+3)=1/2(7-a) | | 3x=5x=2x=4 | | 3z=5z+6 | | -(6+x)-7x=8x-38 | | 267=-5(8n+4)+7 | | -2n-13=-1+n | | 40.97=8g+3.61 | | -0.5(2n+8)=-10 | | 75(x+20)=2+0.5(x-2) | | 5x+7=-8+3x+21 | | 5n/4=35/2 | | 3/4(x+12)=x+5 | | 3x+11=2x–5 | | 3x+5=3x+9-5 | | 5/6=w-5/9 | | -6(2x-1)=-90 | | -(6+x)-7x=8x-32 | | 8x20=2x+34 | | 9x+19x-10=7(4x+5) | | -24x=23-x | | 5(6-4y)-y=21 | | 123.99=172x+19.99 | | 3x+7x+1=(5x+1)+2 | | 3x=243/4 | | 9x+19x-10=7(4x+5 |

Equations solver categories